COMBINATION OF COLD PACK, WATER SPRAY, AND FAN COOLING ON BODY TEMPERATURE REDUCTION AND LEVEL OF SUCCESS TO REACH NORMAL TEMPERATURE IN CRITICALLY ILL PATIENTS WITH HYPERTHERMIA - Nur Eka Dzulfaijah; Mardiyono Mardiyono; Sarkum Sarkum; Djenta Saha (Belitung Raya Foundation, Indonesia, 2017)
Objective: To examine the effect of the combination of cold pack, water spray, and fan cooling on body temperature reduction and level of success to reach normal temperature in critically ill patients with hyperthermia. Methods: This was a randomized control trial (RCT) with pretest posttest control group design and repeated measurement, conducted on December 2016 – January 2017. There were 32 respondents selected using total sampling, with 16 respondents randomly assigned in the experiment and control group. A digital thermometer was used to measure hyperthermia. Paired t-test, Repeated ANOVA with post hoc, and Mann Whitney were used for data analysis. Results: Findings showed that the mean of body temperature in the experiment group in pretest was 38.762 oC and decreased to 37.3 oC after given intervention for 60 minutes. The mean difference of body temperature was 1.4625, with p-value 0.000 (<0.05). In control group, the mean of body temperature in pretest was 38.669 oC and decreased to 38.188 oC given intervention for 60 minutes. The mean difference of body temperature was 0.4812, with p-value 0.000 (<0.05). Conclusion: There was a significant effect of the combination of cold pack, water spray, and fan cooling on body temperature reduction and level of success to reach normal temperature in critically ill patients with hyperthermia. This combination is more effective than water compress alone.